A novel strategy for the synthesis of hollow Pt–Cu tetradecahedrons as an efficient electrocatalyst toward methanol oxidation. Issue 12 (22nd February 2019) - Zhao, Ruopeng; Fu, Gengtao; Chen, Zhijing; Tang, Yawen; Wang, Yi; Huang, Shaoming
Abstract : Pt–Cu TNs can be simply achieved within a few minutes by an H + -assisted disproportionation reaction using Cu2 O tetradecahedrons as the template. Due to its unique structural advantages, these Pt–Cu TNs exhibit extraordinary electrocatalytic performance toward MOR. Abstract : Various bimetallic hollow structures have been widely reported in literature for their excellent catalytic performance. However, researchers still face challenges in tailoring the structures by an efficient and economical method. Herein, we reported a novel, facile and efficient synthetic strategy to synthesize platinum–copper alloy tetradecahedrons (Pt–Cu TNs) with hollow structures by using tetradecahedral Cu2 O as a starting template; we also controlled the thickness of the shell and Pt/Cu ratio. The structure and the formation mechanism of Pt–Cu TNs were investigated in detail. Such Pt–Cu TNs exhibited significantly enhanced activity, stability and CO tolerance ability for the methanol oxidation reaction (MOR) compared with a commercial Pt black catalyst. This can be attributed to their higher specific surface area, easy access for reactants to the catalyst surface, rough surfaces, and the synergistic effect between Pt and Cu.